Mechanism of Pantoea ananatis in the biocontrol of rice bacterial leaf blight - Tian, Ye; Lei, Wenting; Zhang, Jiayi; Shen, Ying; Lu, Jianfei; Ijaz, Munazza; Alrafaie, Alhassan; Ahmed, Temoor; Yan, Chengqi; Li, Bin (Frontiers in Microbiology, 2026)
IntroductionRice bacterial leaf blight, caused by Xanthomonas oryzae pv. oryzae (Xoo), is a highly destructive disease. Within the rice-Xoo pathosystem, Pantoea ananatis exhibits a dual role, functioning both as a pathogen and as a biocontrol agent, underscoring the need to clarify its speciffc functions for effective disease management.MethodsIsolated strains ZJU1-ZJU18 were identified using multi-locus sequence analysis, core-genome phylogenomic analysis, and average nucleotide identity. The population density of Xoo in rice leaves was determined by plate counting and qPCR to evaluate the inhibitory effect of P. ananatis on its growth.Results and discussionThe isolated strains ZJU1-ZJU18 were all identiffed as P. ananatis, and they exhibited plant growth-promoting traits, including phosphate solubilization, siderophore production, and indole-3-acetic acid synthesis. Furthermore, strains ZJU1-ZJU18 did not induce rice bacterial leaf blight symptoms under the experimental conditions, with the lesion inhibition rate against this disease ranging from 95.14 to 97.92%. Mechanistic investigations revealed that P. ananatis suppressed Xoo via nutrient competition, dominating co-culture systems (>90% relative abundance) and reducing Xoo colonization on rice leaves by 96.78–99.00%. Xoo infection enhanced P. ananatis colonization, likely by modifying the leaf microenvironment. Furthermore, the results of species composition analysis showed that P. ananatis could alter the structure and diversity of the microbial community in rice leaves and reduce the abundance of Xanthomonas species. The principal coordinate analysis indicated that P. ananatis had a more signiffcant impact on the microbial community composition than Xoo. This study found that P. ananatis may inhibit the pathogen Xoo through nutrient competition and reshape the microbial structure at the community level.